A CSR Journey: Pemuda Mandiri Pengelola Sampah Pantai Loji PT PLN Indonesia Power UBP Jabar 2 Pelabuhan Ratu - Muhammad Saghar Septian; Aliecya Zahraa Salshabilla; Robert David Carniago; Yovi Alkausar; Asep Tresna Lukman Hakim (Prospect Publishing, 2025)
PERMADANI Program – Entrepreneurship Youth Managing Loji Beach Waste – is a community empowerment program in Loji Village that focuses on environmental conservation efforts. Piles of beach and household wood waste have piled up along Talanca Loji Beach, downstream of the Cimandiri River. This has finally become a serious threat that disrupts the Pelabuhan Ratu PLTU business process, which is located across the beach. Therefore, the PERMADANI program was formed. The PERMADANI program carries out two main activities to reduce waste: (1) biomass co-firing production from shredded seawood waste (and (2) craft production from the Garuda Karya Sapta derivative group. The method in the empowerment process uses a participatory approach by placing the community as the subject of the empowerment itself.